2014
DOI: 10.3892/ijmm.2014.1870
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1-7) attenuates damage to podocytes induced by preeclamptic serum through MAPK pathways

Abstract: The underlying mechanisms of proteinuria, a main characteristic of preeclampsia (PE), have not yet been fully elucidated. Evidence indicates that the renin-angiotensin system (RAS) is involved in the pathogenesis of this disease, including decreased angiotensin-(1-7) [Ang-(1-7)] levels in the circulation and urine. In the present study, we examined the damage to podocytes induced by preeclamptic serum and the effects of Ang-(1-7) on podocytes treated with preeclamptic serum, as well as the underlying mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…To identify the possible novel mechanism underlying TRPC6-calcium/calcineurin signaling activation induced by AT1-AA, we detected the expression of ERK1/2. AT1-AA increased ERK1/2 protein expression, which is in agreement with our previous study [33]. When ERK1/2 inhibitor was administered in the podocytes treated with AT1-AA, we observed marked ameliorations in podocyte injury and a reduction of TRPC6; however, the expression of ERK1/2 was unrecognizable when we knocked down TRPC6.…”
Section: Discussionsupporting
confidence: 80%
“…To identify the possible novel mechanism underlying TRPC6-calcium/calcineurin signaling activation induced by AT1-AA, we detected the expression of ERK1/2. AT1-AA increased ERK1/2 protein expression, which is in agreement with our previous study [33]. When ERK1/2 inhibitor was administered in the podocytes treated with AT1-AA, we observed marked ameliorations in podocyte injury and a reduction of TRPC6; however, the expression of ERK1/2 was unrecognizable when we knocked down TRPC6.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, Ang-(1-7) treatment resulted in a significant decline in the expression and cleavage of caspase-3, a hallmark of apoptosis [28], in the pancreas. The antiapoptotic activity of Ang-(1-7) has also been described in other types of cells, such as human umbilical vein endothelial cells [33], podocytes [29], and alveolar epithelial cells [30].…”
Section: Discussionmentioning
confidence: 97%
“…15, 16, 37 In addition, the p38 MAPK pathway was shown to have an important role in podocyte injury. 38, 39 The data obtained in this study showed that the expression of p-p38 is significantly enhanced in the DN glomeruli and HG-induced MPC5 cells, and it is accompanied by the increase in the expression of Bax and cleaved caspase 3. The inhibition of Mtdh led to the suppression of the activation of p38 MAPK pathway following the HG treatment, which suggests a possible link between Mtdh and p38 MAPK activation.…”
Section: Discussionmentioning
confidence: 52%